CD8αα+T cells exert a pro‐inflammatory role in patients with psoriasis - Y. Y. Zhang (Wiley, 2021)
Abstract Background Psoriasis is a common chronic inflammatory disease caused by excessive activation of CD4+T cells, including Th17, Th1 and Th22. The role of CD8+T cells in psoriasis pathogenesis remains poorly understood. Aim To identify the phenotype of CD8+T cells in patients with psoriasis and to investigate its role in the formation of lesions. Methods The phenotype of CD8+T cells in psoriatic lesions was detected by immunofluorescence staining. Flow cytometry was performed to detect their phenotype in peripheral blood. Thereafter, coculture of CD8αα+T cells with autogenous CD4+T cells was performed to investigate the function of CD8αα+T cells in patients with psoriasis. Finally, pro‐inflammatory factors produced by CD8αα+T cells were examined by immunofluorescence staining and flow cytometry. Results Compared to the CD8αβ+T cells, CD8αα+T cell infiltration in psoriatic lesions markedly increased. Moreover, epidermal CD8αα+T cells exhibited tissue‐resident memory T cells (TRM) phenotypes and dermal CD8αα+T cells exhibited effector memory (TEM) phenotypes in psoriatic lesions. Additionally, we found that CD8αα+T cells from patients with psoriasis did not express the markers of regulatory T cells and could promote the proliferation of CD4+T effector cells and produce interleukin‐17 and interferon‐γ. Conclusions Our findings demonstrate that CD8αα+T cells contribute to the pathogenesis of psoriasis by producing pro‐inflammatory factors.